USE OF TARGETED SELECTIVE TREATMENT IN THE CONTROL OF GOAT PARASITISM IN HUMID TROPICS - Marykutty Thomas; K. Syamala (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted to assess the efficacy of Targeted Selective Treatment (TST) based on the Five point check© in reducing faecal egg count and anthelmintic use thereby improving the health status of goats which are naturally infected with gastro intestinal strongyles under the humid tropical conditions of Kerala. Body condition score, FAMACHA©, evidence of nasal discharge, diarrhoea and sub mandibular oedema were included in the Five point check.  Following implementation TST, the use of anthelmintics was reduced from 100% to 39.1 %. There was no marked difference in faecal egg count and health status of goats prior and after TST protocol.